IMPROVING STUDENTS’ MOTIVATION IN STUDYING ENGLISH USING AUDIO-LINGUAL METHOD - Wullur, Alfa; Liando, Nihta V. F.; Rorimpandey, Rinny (Journal of English Language and Literature Teaching, 2023)
This research is based on the students’ motivation in studying English. It intends to prove that students can improve their motivation and it is seen in their achievement in their study. The purpose of this research is to prove that this method is effective in order to improve students’ motivation to learn English. This research is conducted at SMP Negeri 11 Bitung. The subject of this research is a seventh-grade student of SMP Negeri 11 Bitung consisted of 24 students. The design of this research is a pre-experimental design with one group pre-test and post-test design. The data are collected through multiple choice as an instrument and with questionnaires and interviews to support the data. In analyzing the data writers use percentage formula. The result of this research shows that the score of the post-test is higher (72.09%) than the score of the pre-test (44.16%). Based on the fact of the result of this research, it can be concluded that the Audio-lingual method is effective to be applied in class to improve students’ motivation in studying English.